Manajemen Kepala Sekolah Berbasis Itqan Dalam Mengintegrasikan Visi, Misi Dan Program Kerja di SMAN 4 Sungai Penuh - Millah Kamelia; Eva Fitriati; Wisnarni (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the management of the principal based on the values ​​of itqan in integrating the vision, mission and work program at SMAN 4 Sungai Penuh. This study uses a Qualitative type with a Field Research approach, with research informants including the principal and teachers involved in the implementation of school management. Data collection techniques with observation, interviews and documentation, which are analyzed with a descriptive interpretive approach through a process of reduction, presentation, and drawing conclusions simultaneously and repeatedly. The results of the study indicate that the management of the principal based on the values ​​of itqan plays an important role in integrating the vision, mission, and work program of the school. The application of the values ​​of itqan is reflected in four stages, namely (1) Planning the vision, mission and work program is carried out in a participatory manner through team formation (2) Organizing the team based on competency (3) Implementation through structured and directed deliberations, and (4) Supervision through monthly evaluations involving all school members. The application of the values ​​of itqan that emphasize professionalism, accuracy, responsibility, and work perfection is able to build a work culture that encourages the optimal achievement of educational goals at SMAN 4 Sungai Penuh. Thus, this research offers a principal management model based on itqan values ​​in integrating vision, mission, and work programs contextually which has not been widely studied in school management literature.